2022
DOI: 10.20945/2359-3997000000521
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic and nonglycemic mechanisms of congenital malformations in hyperglycemic pregnancies: a narrative review

Abstract: Congenital malformations are more frequently found among children born to mothers with diabetes than in the background population. There are several complex mechanisms involved in the development of congenital malformations in the offspring of mothers with hyperglycemia, such as the overexpression of glucose transporters (GLUTs) 1 and 2, the increased activity of the hexosamine biosynthetic pathway and the reduced expression of the PAX3 gene with a consequent increase in p53 protein expression. These alteratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Hyperglycaemia has been well studied in both human and animal models. Hyperglycaemia during embryogenesis induces hypoxia, leading to reduced PAX3 expression, which can cause CDH [ 30 , 31 ]. Together with these observations, oxidative stress or epigenetic changes induced by inappropriate nutrition during pregnancy, the preconception period, or even much before pregnancy, which are related to low and high MBW, might be one of the presumed mechanisms by which MBW can cause CDH.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperglycaemia has been well studied in both human and animal models. Hyperglycaemia during embryogenesis induces hypoxia, leading to reduced PAX3 expression, which can cause CDH [ 30 , 31 ]. Together with these observations, oxidative stress or epigenetic changes induced by inappropriate nutrition during pregnancy, the preconception period, or even much before pregnancy, which are related to low and high MBW, might be one of the presumed mechanisms by which MBW can cause CDH.…”
Section: Discussionmentioning
confidence: 99%
“…This is in accordance with the findings of previous studies. It has been shown that CL/P is one of the most frequent congenital malformations among mothers with diabetes [ 23 25 ]. One study that examined orofacial clefts among American mothers have found similar results, and reported that pregestational diabetes was significantly associated with CL/P, even after adjustment [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The altered pathways which may lead to a higher incidence of congenital abnormalities in fetuses of OWO mothers are not fully understood, but might be influenced by the higher levels of serum glucose often seen in OWO women periconceptionally and in the early stages of the pregnancy. Maternal hyperglycaemia leads to an increase of glucose levels in the embryonic environment, due to an overexpression of glucose transporters, as well as to oxidative stress and elevated free radical concentration, leading to a decreased expression of embryonic PAX3-gene and increased expression of the p53-gene [ 67 ]. As a consequence, apoptosis is increased which may be the link to the higher prevalence of fetal malformations.…”
Section: Fetal Abnormalities In Overweight and Obese Pregnant Womenmentioning
confidence: 99%